PEROSOMUS HORRIDUS FOETAL MONSTER IN A NON-DESCRIPT COW - SATHIAMOORTHY, T; BISWAL, S S; KALYAAN, U S; SABARINATHAN, A; KESHARI, VINEET; MOHAN, P; SARATH, T; BALASUBRAMANIAN, S (The Indian Journal of Animal Reproduction, 2023)
A rare case of dystocia due to Perosomus horrid us foetal monster in cow and its successful managementby caesarian section was reported.
Keywords: Dystocia; Perosomus horridus foetus; cow